Use of Perennial Grasses in Peanut/Cotton Rotations for Integrated Management of Nematodes, Diseases, and Weeds - David L. Wright; James J. Marois; Sheeja George; Zane Grabau; Rebecca Barocco; Ian Small (EDIS)
This 3-page publication discusses the benefits of using perennial grasses in peanut/cotton rotations for integrated management of nematodes, diseases, and weeds. Written by D. L. Wright, J. J. Marois, S. George, Z. Grabau, R. Barocco, and I. Small, and published by the UF/IFAS Agronomy Department, revised September 2022.